2014
DOI: 10.1002/ps.3857
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the control of apple leaf midge Dasineura mali (Diptera: Cecidomyiidae) by mass trapping with pheromone lures

Abstract: The attractiveness of the pheromone, monophagous habit and low mobility of D. mali enhance the prospects for successful mass trapping. Countering this are high populations, multivoltinism and aspects of mating behaviour. Mass trapping would probably have been more effective had it been in place season long and conducted over successive years. It needs refinements and more study before becoming a feasible control option for D. mali.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…38 Suppression of D. mali appears to be promising from these tests, but other factors can be very important to the outcome, such as multiple mating by males, which is known to be an issue because it dilutes the population suppression effect from a reduced impact on the mating rate of females. 20 High density and reproductive rate as well as female dispersal into the plots at 750 traps ha −1 likely led to shoot damage reductions of only ∼50%, 26 which supports the need for areawide treatment. Treating larger areas with male removal should solve immigration problems.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…38 Suppression of D. mali appears to be promising from these tests, but other factors can be very important to the outcome, such as multiple mating by males, which is known to be an issue because it dilutes the population suppression effect from a reduced impact on the mating rate of females. 20 High density and reproductive rate as well as female dispersal into the plots at 750 traps ha −1 likely led to shoot damage reductions of only ∼50%, 26 which supports the need for areawide treatment. Treating larger areas with male removal should solve immigration problems.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 29 traps (of 750) were cleared in each of four replicate plots. This number was determined as adequate in a related study which indicated sharp boundaries on the edge of plots, with rapid drop in catch inwards …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations